Effect of Ta2O5 doping on the electrical properties of 0.99SnO(2)center dot 0.01CoO ceramic - Antunes, A. C.; Antunes, S. M.; Pianaro, S. A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2000)
The effect of Ta2O5 doping in 0.99SnO(2). 0.01CoO on the microstructure and electrical properties of this ceramic were analyzed in this study. The grain size was found to decrease from 6.87 mu m to 5.68 mu m when the Ta2O5 concentration increased from 0.050 to 0.075 mol%. DC electrical characterization showed a dramatic increase in the current loss and decrease in the non-linear coefficient with the increase of the Ta2O5 concentration. The conduction mechanism is by thermionic emission and the potential barriers are of Schottky type, separated by a thin film. (C) 2000 Kluwer Academic Publishers.